2019 IEEE 16th International Symposium on Biomedical Imaging (ISBI 2019) 2019
DOI: 10.1109/isbi.2019.8759159
|View full text |Cite
|
Sign up to set email alerts
|

Ultracompression: Framework For High Density Compression Of Ultrasound Volumes Using Physics Modeling Deep Neural Networks

Abstract: Ultrasound image compression by preserving specklebased key information is a challenging task. In this paper, we introduce an ultrasound image compression framework with the ability to retain realism of speckle appearance despite achieving very high-density compression factors. The compressor employs a tissue segmentation method, transmitting segments along with transducer frequency, number of samples and image size as essential information required for decompression. The decompressor is based on a convolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Ultrasound (US) imaging in biomedical applications such as image-guided radiotherapy (IGRT) has increased in the last decade because of its non-ionizing nature and real-time imaging capability [1][2][3][4][5][6][7][8][9][10][11][12][13] . The use of other imaging modalities has been more common [14][15][16][17][18][19][20][21][22][23][24] than the use of US-based techniques in clinical applications of IGRT due to the rigid architecture of traditional US probe transducers.…”
Section: Introduction and Purposementioning
confidence: 99%
“…Ultrasound (US) imaging in biomedical applications such as image-guided radiotherapy (IGRT) has increased in the last decade because of its non-ionizing nature and real-time imaging capability [1][2][3][4][5][6][7][8][9][10][11][12][13] . The use of other imaging modalities has been more common [14][15][16][17][18][19][20][21][22][23][24] than the use of US-based techniques in clinical applications of IGRT due to the rigid architecture of traditional US probe transducers.…”
Section: Introduction and Purposementioning
confidence: 99%
“…In another study, Perdios et al [26] presented an approach for ultrasound image recovery where compression and decompression of ultrasound signals were achieved using a stacked denoising autoencoder (SDA). Moreover, China et al introduced an ultrasound image compression system that preserves speckle information, with a CNN-based decompressor generating patho-realistic ultrasound images that convey essential information about pathological tissues [27].…”
Section: Introductionmentioning
confidence: 99%
“…Several efficient beamforming and/or compressive sensing algorithms have been proposed to address such demands [5][6][7][8][9][10]. The dynamic receive beamformer is one of the most complex processing components in a US imaging system; our previous research found that it contains 46.5% of the total hardware resources and 25.4% of the total power consumption of a system-on-chip solution for portable US imaging [11].…”
Section: Introductionmentioning
confidence: 99%